Efektivitas Aplikasi Taspen Otentikasi Dalam Pemenuhan Hak Penerima Dana Pensiun Di Pt. Bank Mandiri Taspen Kota Bengkulu - Dyah Nuri Mardania; Nur Sulistyo Budi Ambarini; Joko Susetyanto; Hamdani (Jurnal Ilmiah Kutei, 2025)
PT Taspen (Persero) issued a digital-based innovation in the form of an authentication taspen application. This authentication taspen application is a requirement in the payment of pension funds. However, there are still obstacles in the use of taspen authentication application. This research uses empirical law or law in action research methods. This research uses primary data and secondary data obtained through direct interviews and document studies. The data obtained will be processed by editing techniques and then analyzed by qualitative analysis methods. The result of this research is the Taspen Authentication Application in fulfilling the rights of pension fund recipients at PT. Bank Mandiri Taspen Bengkulu City has not been effective because not all pension fund recipients can use the Taspen Authentication Application so that there is a delay in fulfilling the rights of pension fund recipients. While in fulfilling the rights of participants receiving pension funds due to failed authentication in the Taspen Application at PT Bank Mandiri Taspen Bengkulu City, PT Bank Mandiri Taspen Bengkulu City provides 3 (three) solutions that can be carried out by participants receiving pension funds according to the obstacles and physical conditions of the participants receiving pension funds, namely manual authentication through customer service (CS), power of attorney, customer visit services (LKN).